OC-084 The clonal progression of barrett's oesophagus to oesophageal adenocarcinoma. (28th May 2012) - Khan, S; Zeki, S; Mitchell, I; Harrison, R; Dunn, L; Leedham, S; Barr, H; Shepherd, N; Graham, T; Wright, N; McDonald, S
Abstract : Introduction: Barrett's oesophagus (BO) is a common premalignant condition, wherein the normal squamous oesophageal epithelium is replaced by a columnar, intestinal phenotype. It is the predominant risk factor for the development of oesophageal adenocarcinoma (OA) 1 which develops through a metaplasia: dysplasia: carcinoma sequence. Initial studies suggested that BO lesions were genetically clonal. 2 However; our group has shown, by gland micro-dissection, that multiple clones are present within BO and it is therefore a genetically heterotypic disease. 3 Furthermore, Maley et al 4 have shown that genetic diversity increases the risk of BO progressing to cancer. Here, we demonstrate that although Barrett's dysplasia is polyclonal, oesophageal adenocarcinomas arising from Barrett's are typically clonal. Methods: DNA was macro-dissected from dysplastic and cancerous regions of endoscopic mucosal resection (EMR) and oesophagectomy specimens and screened for mutations in p16 INK4A, TP 53 and K-RAS . Mutated specimens were serially sectioned; crypts and carcinomas were histologically graded and then micro-dissected using a P.A.L.M. laser capture microscope. DNA was extracted from dissected material and was sequenced for the point mutations identified in the initial screen. Results: Individual glands from 10 specimens (EMRs and oesophagectomies) were laser captured and sequenced for mutations identified as per above. Seven specimens contained TP53 mutations and the three remaining specimens were mutated for p16 INK4A . Overall, seven of these specimens contained both mutated and wild type dysplastic glands, with a further one specimen containing three distinct p16 INK4A mutation. However, the related cancers from these specimens were monoclonal for a mutated genotype found in the dysplasia. These data show that Barrett's dysplasia is polyclonal but Barrett's adenocarcinoma is monoclonal, suggesting that a cellular competition may be involved in the evolution of Barrett's adenocarcinoma from its surrounding dysplasia. Conclusion: Barrett's dysplasia exhibits a mosaic pattern of clones, indicating genetic diversity in Barrett's dysplasia. Oesophageal adenocarcinomas were monoclonal outgrowths from polyclonal Barrett's dysplasia. Competing interests: None declared. References: 1. Jankowski JA, et al. Gastroenterology 2002;122 :588–90. 2. Galipeau, et al. J Natl Cancer Inst 1999;91 :2087–95. 3. Leedham, et al. Gut 2008;57 :1041–8. 4. Maley C, et al. Nature Genetics 2006;38 :468–73.